Rekomendasi Pemilihan Pemain Sepak Bola Terbaik Pada Liga X Menggunakan Metode Topsis - Oki Iskandar; Gunawan Abdillah; Agus Komarudin (Prosiding SISFOTEK, 2020)
Football is a popular sport that is widely played. Proved by the number of competition titles held. Every team that competes, will provide competitive competition. Players who play an important role in presenting competitive competition. Competition that occurs is not only the team that competes but all players take part in the competition to be the best. Each competition will reward each of the best players throughout the competition. The many factors and players involved make it difficult for the organizers to determine the best player. Decision support system is a computer-based system that can manipulate data into information that can provide alternative decisions or problem solving, so that data can be processed into information. Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is a multi-criteria decision making method or has many criteria. This research resulted in a decision support system that can be used to choose the best soccer players by using a combination of individual ability criteria, contribution to the team, aspects of fair play and the number of minutes played. By using the TOPSIS method, as many as 11 player data were tested and resulted in a suitability level of 57.14%.